2021
DOI: 10.1186/s12903-021-01485-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between psychological factors and temporomandibular disorders in adolescents of rural and urban zones

Abstract: Background Temporomandibular disorders (TMD) are related to psychological factors. Adolescence is one of the stages in life with more psychosocial vulnerability, which is dissimilar in rural and urban zones. Thus, the aim of this investigation was to evaluate the association between psychological factors (symptoms of anxiety, depression and somatization) and TMD in adolescents between 12 and 15 years, belonging to urban and rural zones of Colombia. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 47 publications
0
21
0
7
Order By: Relevance
“…Further, due to the study design, it was not possible to extrapolate the results of TMD prevalence to the entire Peruvian population, so more epidemiological studies are needed in Peru, with a large scope, that apply the SFAI for the identification of TMD. However, apart from the constant monitoring of the temporomandibular joint in patients with related symptomatology due to anxiety or stress disorders,[ 5 12 , 34 ] bruxism, and partial edentulism, among others,[ 10 32 ] being necessary, it would be very useful to use the SFAI as a rapid diagnostic test to detect TMD in large populations where it is required to evaluate the largest number of people in a relatively short time and at low cost. It is recommended that more studies of predictability and precision of the SFAI be carried out in different regions of Peru and Latin America, in order to evaluate possible exogenous variables that affect its predictive efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, due to the study design, it was not possible to extrapolate the results of TMD prevalence to the entire Peruvian population, so more epidemiological studies are needed in Peru, with a large scope, that apply the SFAI for the identification of TMD. However, apart from the constant monitoring of the temporomandibular joint in patients with related symptomatology due to anxiety or stress disorders,[ 5 12 , 34 ] bruxism, and partial edentulism, among others,[ 10 32 ] being necessary, it would be very useful to use the SFAI as a rapid diagnostic test to detect TMD in large populations where it is required to evaluate the largest number of people in a relatively short time and at low cost. It is recommended that more studies of predictability and precision of the SFAI be carried out in different regions of Peru and Latin America, in order to evaluate possible exogenous variables that affect its predictive efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…To diagnose the different TMDs, different indexes have been created, with the Helkimo Index being one of the most used and widely accepted, since it has withstood the test of time for being simple and practical, allowing it to quantify the existing dysfunction and also allowing it to correlate the patient’s symptoms and the clinical finding, in comparison to other clinical indexes. [ 10 11 ] However, the Helkimo Index was later modified by Maglione[ 12 13 ] in 1982 in order to improve the determination of severity. On the other hand, it should be recognized that this high instrument accuracy requires the application of clinical procedures that require a considerable amount of time, a situation that is not useful for studies in large populations.…”
Section: Introductionmentioning
confidence: 99%
“…Dos artigos incluídos nesta revisão, 7 abordavam aspectos psicossociais e sua relação com a pandemia por COVID-19 (Di Blasi et al, 2021;De Boni et al, 2020;Gutiérrez-Hernández et al, 2021;Limcaoco et al, 2020;Liao et al, 2021;Liu et al, 2021;Wang et al, 2021), 5 apresentavam os aspectos psicossociais e sua relação com DTM (Alahmary, 2019;Guimarães;Almeida, 2018;Canales et al, 2019;Yap;Natu, 2020;Zavanelli, 2017) e 7 dissertavam sobre a associação entre as alterações psicológicas causadas pela pandemia por COVID-19 e sua relação com bruxismo e DTM (Asquini et al, 2021;Emodi-Perlman et al, 2020;Gaş;Özsoy;Aydin, 2021;Medeiros et al, 2020;Restrepo et al, 2021;Saccomanno et al, 2020;Silva et al 2021).…”
Section: Discussionunclassified
“…Houve correlação positiva entre comportamentos orais e sintomas de DTM, ansiedade e depressão. Restrepo et al, 2021 Estudo transversal. Avaliar a associação entre fatores psicológicos (sintomas de ansiedade, depressão e somatização) e DTM em adolescentes entre 12 e 15 anos, pertencentes às zonas urbana e rural da Colômbia.…”
Section: Liao Et Al 2021unclassified
“…Mouth-opening limitation, oral and maxillofacial pain, and joint clanging are the most common symptoms, which severely affects the quality of life of patients with TMD [ 1 , 2 ]. Anxiety, depression, somatization, and other psychological factors are closely related to the generation of TMD [ 3 , 4 ]. Epidemiological study has shown that about 10% of the population is affected by TMD, especially in 30-year-old women [ 5 ].…”
Section: Introductionmentioning
confidence: 99%